Characterization and efficacy of white-rot hymenomycetes in biodegradation of oil palm wood logs and suppression of Ganoderma boninense - Raju Naidu, Yuvarani Naidu (2018)
Sustainability of oil palm production in South-East Asia is jeopardized by Ganoderma boninense, the causal agent of basal stem rot (BSR) in oil palm. Root-to-root contact is a major mode of disease spread, and oil palm debris left unattended in fields is an important source of inoculum. Amongst several control methods, expulsion of debris, before replanting is currently being practiced. The present research investigated potential white-rot hymenomycetes as an antagonist to degrade Ganoderma infected oil palm log blocks and suppressed BSR infection pressure by reducing the inoculum spread. A total of 100 fungi had been isolated from the fruiting bodies occurring naturally on oil palm trunks. Of them, twenty-five Basidiomycetes were isolated on a Ganoderma selective medium and identified using internal transcribed spacer (ITS) DNA sequencing. The potential hymenomycetes were evaluated on their dual characteristics of biocontrol and biodegradation that could be opted in reducing G. boninense inoculum during oil palm replantation. Three fungi with potentially higher antagonistic activity based on percentage inhibition radial growth against G. boninense, were Pycnoporus sanguineus FBR (84%), Trametes lactinea FBW (82%) and Grammothele fuligo ST2 (81%). Additionally, Lentinus tigrinus FBJ G3 and a Rigidoporus sp. STB also invaded sterilized G. boninense colonized oil palm wood blocks. Colonization of oil palm blocks by these isolates resulted in mass losses ranging from 66 to 79% after 120 days of biodegradation periods. During early decay period, P. sanguineus FBR selectively removed the wood lignin, prior to wood polysaccharides, whereas L. tigrinus FBJG3 and T. lactinea FBW preferentially degraded the wood polysaccharides prior to lignin degradation. In contrast, G. fuligo ST2 simultaneously degraded the lignin, cellulose, hemicellulose and preferentially the starch components deposited mostly in the parenchymal tissue of the oil palm wood blocks. This phenomenon was supported with the anatomical and chemical characterization (FTIR) studies. Scanning electron microscopy revealed the ingression and colonization of fungal mycelium with clamp connections within wood vessels and parenchymatic tissues. Besides, formation of boreholes as round spots were apparent, followed by loosening and formation of large cavities on the ray of the parenchymatic cells as the decay progressed. Based on the pathogenicity and vegetative growth assessments on oil palm seedlings, seven isolates can be affirmed nonpathogenic to oil palm seedlings. Out of that, four potential strains (Trametes lactinea FBW, Pycnoporus sanguineus FBR, Lentinus tigrinus FBJ G3, and Grammothele fuligo ST2) were selected for mass production on agro-industrial wastes. Six solid-substrates were tested for mass production of the hymenomycetes. Amongst them, two solid substrates that yielded optimum lignocellulolytic enzymes production, namely (1) empty fruit bunches inoculated with P. sanguineus FBR and (2) combination of rubber wood sawdust and vermiculite inoculated with the strain of T. lactinea FBW were tested for log blocks treatment in accelerating the decaying process and recovery of Ganoderma inoculum. Weight lossess of 64% (T. lactinea FBW), 55% (P. sanguineus FBR) and 23% (un-inoculated) were obtained after 10 months of log blocks treatment. Similarly, lowest recovery of Ganoderma spp. was reported in log blocks inoculated with T. lactinea FBW (21%) and P. sanguineus FBR (33%) in comparison to that of treated with the formulations alone (without hymenomycetes). The nursery study supported the in vitro investigation, which had reported T. lactinea FBW and P. sanguineus FBR as the potential antagonist against Ganoderma inoculum. Furthermore, production of enormous lignocellulolytic enzymes owe to their efficient bio-degrading ability. This study provides great insight of the lignocelluloses degradation mechanisms and processes by these white-rot hymenomycetes. Additionally, an alternative biotechnological approach has been identified in degrading infected oil palm logs thus, reducing Ganoderma inoculum pressure in eco-friendly manner.